When should Romania join the European banking union, sooner or later? - Laurian Lungu; Ella Viktoria Kállai (European Institute of Romania, 2015)
The emergence of the financial crisis back in 2007 exposed a series of deficiencies in the way the European mechanisms functioned, highlighting the incomplete policy design of the EMU (Economic and Monetary Union). Thus, it became evident that financial integration, financial stability and national responsibility for crisis prevention and management could not be all simultaneously fulfilled. Several factors have been responsible for the deepening of the financial crisis effects in the EU (European Union)/EZ (Euro Zone), namely the one-size fits all monetary policy and the absence of a fiscal institution counterpart to the ECB (European Central Bank), the EZ governance focused on rules-based prevention with limited scope for crisis management, lax banking supervisory standards, the absence of cross-border risk sharing mechanisms and bank nationalism, and the lack of political leadership. Given these flaws, the aims of the EBU (European Banking Union) would largely be twofold: * To strengthen the single market for financial services by ensuring a level playing field for banks. This would require a competitively neutral financial supervision across the EZ (and ideally across the EU). * To break the vicious circle between sovereigns and banks, thus reversing the process of financial fragmentation. [...]
Keywords: 330